CYCLOPENTYL TRISILANOL SILSESQUIOXANES – MODIFIED NATURAL RUBBER (CpSSQ(OH)3– ENR-50) NANOCOMPOSITE IN THE PRESENCE OF TIN (II) CHLORIDE DIHYDRATE - H. Rosniza; M. A. Bakar; S. Abdul Hamid; J. Ismail (Indonesian Journal of Chemistry, 2007)
A nanocomposite comprising cyclopentyl trisilanol silsesquioxanes (CpSSQ(OH)3) and 50% epoxidized natural rubber (ENR-50) was prepared at reflux temperature with Tin (II) chloride dihydrate (SnCl2.2H2O) as catalyst. SnCl2.2H2O was found to be an affective catalyst to promote ring opening in ENR-50 and tailored it to CpSSQ(OH)3 via chemical reaction. The generation of carbonyl functional groups arising from epoxide ring opening can be clearly seen in FTIR spectra. 1H and 29Si NMR analyses further proved that the incorporation of CpSSQ(OH)3 in  ENR-50 occured. TGA studies showed a degradation temperature with 10% weight decreased and DSC thermogram indicates a single Tg. Single peak in XRD diffractogram at 2-Theta angle further confirmed the surface modification.